Transgenerational seasonal timer for suppression of sexual morph production in the pea aphid, Acyrthosiphon pisum. (August 2017) - Matsuda, Naoki; Kanbe, Takashi; Akimoto, Shin-ichi; Numata, Hideharu
Graphical abstract: Highlights: A transgenerational seasonal timer suppresses sexual morph production in aphids. The seasonal timer depends on the number of days through generations after hatching. Temperature affects the duration of the seasonal timer, whereas photoperiod does not. Abstract: Many aphid species switch reproductive modes seasonally, with the sexual generations appearing in autumn. Sexual generations are induced by short days. It has been reported that the appearance of sexual morphs is suppressed by a transgenerational factor (a seasonal timer) over several generations after hatching from overwintered eggs. The present study examined whether the seasonal timer measures the number of days from hatching or the number of generations from hatching using the pea aphid, Acyrthosiphon pisum Harris (Homoptera: Aphididae). Effects of temperature and photoperiod on the seasonal timer were also examined by successive rearing. The ability to produce sexual morphs was strongly suppressed in stem mothers (the foundress generation), and gradually recovered over successive generations produced during a few months. The duration for which the seasonal timer could function depended on the number of days from hatching and temperature, but not on photoperiod or the number of generations from hatching. We thus showed in a single study that the seasonal timer of the pea aphid has all the physiological characteristics shown in separate studies in different aphid species.